Cavity-excited Huygens’ metasurface antennas for near-unity aperture illumination efficiency from arbitrarily large apertures - Ariel Epstein (Nature Portfolio, 2016)
The realization of highly-directive beams using low-profile devices has been a long-standing problem. Here, Epstein et al.demonstrate a cavity-excited Huygens’ metasurface antenna, where the single-source-fed cavity is designed to optimize aperture illumination, while the metasurface facilitates phase purity.